Mice with targeted mutations of glucocorticoid and mineralocorticoid receptors: Models for depression and anxiety? - Gass, Peter; Reichardt, Holger Michael; Strekalova, Tatyana; Henn, Fritz A.; Tronche, François (Physiology & behavior, 2001)
Impaired corticosteroid receptor signaling is a key mechanism in the pathogenesis of stress-related psychiatric disorders such as depression and anxiety. Since in vivo expression and functional studies of corticosteroid receptors are not feasible in the human central nervous system, such analyses have to be done in animal models. Transgenic mice with mutations of corticosteroid receptors are promising tools, which allow us to investigate the role of these proteins in the pathogenesis of symptoms characteristic for depression and anxiety. This review summarizes the neuroendocrinological and behavioral findings that have been obtained in six different mouse strains with specific mutations that influence the expression or the function of the glucocorticoid or the mineralocorticoid receptor (MR). The analyses of these mice helped to define molecular concepts of how corticosteroid receptors regulate the activity of the hypothalamic-pituitary-adrenal (HPA) system. Furthermore, some of these mutant mice exhibited characteristic alterations in behavioral tests for anxiety and despair. However, so far, none of the mouse strains described here can be viewed as an animal model of a specific psychiatric disease defined by common diagnostic criteria. Using high throughput technologies for the identification of genes regulated by glucocorticoid receptor (GR) and MR in brain areas responsible for specific symptoms of stress-related disorders will yield potential new drug targets for the treatment of depression and anxiety.